TAX ADMINISTRATION STRATEGIES AND PERFORMANCE OF STATE INTERNAL REVENUE SERVICES IN SOUTH-WEST NIGERIA - Mubaraq Sanni; Samuel Kayode Adekunle; Abdul Garba (Malete Journal of Accounting and Finance)
The dwindling pattern of revenue received by states from the central government of Nigeria, especially in the period of falling oil price constitutes a serious challenge to governments in fulfilling their contractual obligations. Consequently, governments across states charge their internal revenue agencies to innovatively pursue revenue mobilisation through various strategies within the chain of tax administration practice. The extents to which all the deployed strategies have effectively yielded more revenue deserve systematic inquiry. Thus, the study investigated the relationship between tax administration strategies and performance of state’s internal revenue services in South West Nigeria. To achieve this objective, quantitative method was employed to obtain survey data from randomly selected 382 revenue officers out of the total population of 8,734 staff of state internal revenue services in South-West Nigeria. The obtained quantitative data was subjected to both descriptive analysis and Partial Least Squares (PLS-SEM) regression analysis. The findings of the study revealed that revenue collection strategy (β=0.104, t-value=18.114, P-value<0.05); Staff compensation strategy (β=0.153, t-value=2.291, P-value <0.05) and Tax advocacy strategy (β=0.106, t-value=5.349, P-value<0.05) have significant positive impact on the revenue performance of state internal revenue service in South West Nigeria. Based on result of analysis, the study concludes that all strategies deployed within the chain of tax administration practice are effective in enhancing revenue capacity of the State Government’s in the South West of Nigeria. Therefore, the study recommends that governments should intensify efforts through adequate funding for the deployment of strategies in the areas of revenue collection, advocacy and staff incentives to enhance revenue generating capacity of states in South West Nigeria.